National Identity and Conceptual Art: The Saudi Society - Rihab Abdullah Alghathami , Assistant Professor (lark, 2023)
This study reveals the constituent elements of the Saudi national identity and the possibility of benefiting from them to produce conceptual artworks. The study aims to transform the constituent elements of the Saudi national identity into a conceptual work that contributes to boosting and consolidating national identity among members of the society.The research adopted the descriptive analytical method through a description and analysis of the components of the Saudi national identity. Additionally, the research implemented an experimental approach by conducting a self-artistic experiment of the researcher/artist to produce an artistic conceptual work of art that reflects the Saudi national identity. Among the results achieved by the study is the possibility of producing conceptual artworks that carry multiple messages to consolidate and boost the Saudi national identity. Furthermore, the elements of national identity are characterised by formal, intellectual and cultural richness. The study recommends the need for conducting research similar to the present study to enhance the national identity through contemporary art, along with the need to produce conceptual artworks to strengthen the national identity among recipients.
Keywords: Visual art, contemporary art, artistic work, artistic criticism, artistic metaphor, Saudi identity